Awareness of genetically modified products among Malaysian consumers - Muhamad Afiq Faisal, Y.; Mohd Faizal, H. (2016)
Genetic modification technology allows scientists to alter the genetic information of a particular organism. The technology allows the production of genetically modified organism (GMO) that has the enhanced property compared to the unmodified organism. The application of such technology is not only in agriculture industry, it is now has been applied extensively in biopharmaceutical industry such as transgenic vaccines. In Malaysia, Biosafety Act 2007 has been enacted in which all GMO-based products must be labeled with adequate information before being marketed. This paper aims to determine the awareness level amongst Malaysian consumers on the GM products available in the market and the efficiency of information supplied in the GM product labeling. The result of the survey will serve as a guideline for Malaysia government agency bodies to provide comprehensive yet efficient information to consumers for the purpose of GM product labeling in the near future. In conclusion, the efficiency of information delivery plays a vital role in ensuring that the information is being conveyed clearly to Malaysian consumers during the selection process of GM products available in the market.